Making Microfinance Work Better in the Middle East and North Africa - Brandsma, Judith; Hart, Laurence (World Bank, Washington, DC, 2016)
This report analyzes microfinance in the Middle East and North Africa, and offers recommendations on how to further develop the industry. Microfinance is the provision of financial services to the entrepreneurial poor, a definition with two important features: it emphasizes a range of financial services-not just credit-and it emphasizes the entrepreneurial poor. The region's emerging microfinance industry differs from those in other parts of the world. Expectations are too high: microfinance is not a panacea for, or solution to unemployment, for narrowly defined, most microfinance institutions only offer credit for business activities, and do not offer savings or deposit services. Governments are interested in regulating microfinance, and several countries have passed laws on microfinance, efforts that risk jeopardizing the industry's healthy development. Moreover, second generation issues may slow the industry's growth, demonstrated by the fact that many microfinance institutions are experiencing crises, after rapid initial growth, and need time to consolidate and restructure. Islamic finance methodologies are being applied by new microfinance programs, and existing programs that use Islamic finance-some of them very large-have become more visible. This report draws heavily on two Bank surveys of microfinance institutions in the region, one assessing developments as of the end of 1997, and the other as of end of 1999. Egypt remains the region's leading provider but has lost market share, while Morocco is second, having experienced dramatic growth since 1997. But other countries, such as Lebanon, and the West Bank and Gaza, saw their microfinance industries stagnate, or even shrink. This was mainly because microfinance players in these countries went through restructuring, and consolidation as they faced second generation issues. The report stipulates that for programs to reach the scale of microfinance institutions as in other parts of the world, they must raise funds commercially-including taking deposits, which will also enable them to broaden their approach to microfinance, moving beyond credit for businesses. And, by mobilizing savings and deposits, they will be able to serve many more clients. Donors and practitioners alike, should be prepared for the array of new training needs, deciding to transform into a new legal entity, and institutional form. Policymakers, meanwhile, should be prepared to create legal environments appropriate for prudent, but growing microfinance.